Intravenous thrombolysis in patients with acute ischaemic stroke with history of prior ischaemic stroke within 3 months - Tsivgoulis, Georgios; Katsanos, Aristeidis H.; Schellinger, Peter D.; Köhrmann, Martin; Steiner, Thorsten; Caso, Valeria; Palaiodimou, Lina; Strbian, Daniel; Ahmed, Niaz; Alexandrov, Andrei; Savitz, Sean I. (Journal of neurology, neurosurgery, and psychiatry, 2019)
Current guidelines from the American Heart Association/American Stroke Association advocate against the administration of intravenous thrombolysis (IVT) in patients with acute ischaemic stroke (AIS) with a prior ischaemic stroke (IS) within 3 months (Class III: Level of Evidence B).1 This concern is based on a presumed increased risk of symptomatic intracranial haemorrhage (sICH) and mortality2 and therefore led to the respective guideline recommendation. Thus, patients with a history of prior IS have been excluded in the majority of the pivotal randomised controlled clinical trials that have established IVT as a treatment for AIS.2 - - However, the rationale for excluding patients with a history of IS within the prior 3 months in the aforementioned trials was not based on pathophysiological considerations but instead on information extrapolated from the relevant recommendations for IVT in myocardial infarction.2 In the present systematic review and meta-analysis, we sought to compare the safety and efficacy of IVT treatment between patients with AIS with a history of previous IS within 3 months and patients with AIS but without a history of previous IS within 3 months from the index event. - - This meta-analysis is presented according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for systematic reviews and meta-analyses. - - From eligible studies, we extracted data on the primary safety outcomes of sICH (according the definition used in each study) and in-hospital or 3-month mortality. We also evaluated the following efficacy outcomes: early neurological improvement (ENI) at 24 hours (according to the definition used in each study), 3-month favourable functional outcome (FFO, modified Rankin Scale (mRS) scores 0-1), 3-month functional …